2012
DOI: 10.1063/1.3680092
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport anisotropy of buckling graphene under uniaxial compressive strain: Ab initio study

Abstract: Electronic transport properties of graphene under uniaxial compressive strain are studied using ab initio calculations. With approximate thermal perturbation, buckling occurs when strain exceeds a threshold, comparing to flat unperturbed structures. Transmissions of flat graphene compressed along zigzag direction (ZCG) and buckled graphene compressed along armchair direction (ACG) are insensitive to strain, whereas those of buckled ZCG and flat ACG are negatively correlated to strain. Flat graphene has anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is reported that buckling occurs when strain exceeds a threshold, and that flat graphene has anisotropic resistance along the strain direction, while buckling suppresses the anisotropy by releasing the strain. (c)-(d) Illustration of buckling generation in side views [19].…”
Section: A Ab-initio Study Of Nanomaterialsmentioning
confidence: 99%
“…It is reported that buckling occurs when strain exceeds a threshold, and that flat graphene has anisotropic resistance along the strain direction, while buckling suppresses the anisotropy by releasing the strain. (c)-(d) Illustration of buckling generation in side views [19].…”
Section: A Ab-initio Study Of Nanomaterialsmentioning
confidence: 99%
“…Therefore, the buckling of graphene is one of the most important mechanical responses [8]. Buckling-driven wrinkles effectively influence the gauge field [9,10], electronic structure [11,12], Raman spectroscopy [13,14], electronic transport [15,16] and carrier mobilities [17] in graphene sheets. In addition, the growing interest in the exploitation of graphene as nanoreinforcement [18,19] makes it important to understand the buckling effect of graphene in these composites [20].…”
Section: Introductionmentioning
confidence: 99%